Case report series: revisiting third and fourth pharyngeal arch anomalies, − are they thymopharyngeal duct remnants? - A. O. Kotwica; J. Rudd; D. J. Howard (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Pharyngeal arch anomalies are the second most common form of head and neck congenital defect. The second arch anomalies are the most common, and compromise 95% of cases. Little is known about the 3rd and 4th arch anomalies as they are extremely rare. They most commonly present in childhood with sudden severe left lateral neck infection and abscess formation with considerable tendency to recur, contributing to significant mortality and morbidity in those patients. Case presentation Here we present four cases finally diagnosed as third or fourth pharyngeal arch anomalies, with more than 20 years of follow-up following their definitive surgery. The possibility that they are thymopharyngeal duct remnants is discussed. Conclusion Meticulous open radical surgical excision of all involved paralaryngeal, parapharyngeal and thyroid tissue, with preservation of the superior and recurrent laryngeal nerves, is required for cure of recurrent cases. Graphical abstract